Constitutionalism and the rule of law : bridging idealism and realism / edited by Maurice Adams, Anne Meuwese, Ernst Hirsch Ballin. - Adams, Maurice, 1964-; Meuwese, Anne Claartje Margreet, 1980-; Hirsch Ballin, E. M. H. (Cambridge University Press, 2017)
Rule of law and constitutionalist ideals are understood by many, if not most, as necessary to create a just political order. Defying the traditional division between normative and positive theoretical approaches, this book explores how political reality on the one hand, and constitutional ideals on the other, mutually inform and influence each other. Seventeen chapters from leading international scholars cover a diverse range of topics and case studies to test the hypothesis that the best normative theories, including those regarding the role of constitutions, constitutionalism and the rule of law, conceive of the ideal and the real as mutually regulating.